De la petite chanson aux rafales du vent : le parcours de la ritournelle dans l’œuvre poétique d’Emily Brontë - Charlotte Borie (Cahiers Victoriens et Edouardiens)
According to Gilles Deleuze and Félix Guattari, the ritornello’s first formulation is the little song a child sings to himself to find comfort when alone in the dark. It is a sound that repeats itself, forms a centre, becomes a motif, ends up coming in a rhythmic contact with what surrounds the territory it has created, until it vibrates in harmony with the Cosmos. This little song is to be found in Emily Brontë’s poetry, repeating itself, evolving, up until its essence is finally endorsed by the voice of the wind which woos the poet into a poetic transe. The incantatory resurgence of the ritornello punctuates the poetic mind’s trip from fancy to imagination, along which the idea of return applies less to the memory than to the repressed.